Ethanol dry reforming over lanthanide-promoted Ni/A12O3 catalysts for syngas production - Mahadi, Bahari (2017)
Ethanol dry reforming has been regarded as an alluring and promising approach since it consumes greenhouse gas, CO2 and renewable bio-component of ethanol to generate value-added products. Ni-based catalysts are the conventional reforming catalysts due to their high capacity of C-C and C-O bond cleavage. However, these catalysts suffer from sintering and deposited carbon formed from ethylene polymerization, Boudouard and methane decomposition reactions. Therefore, the aim of this thesis was to investigate the effect of promoters (CeO2 and La2O3) and promoter loading on the physicochemical properties of 10%Ni/Al2O3 catalyst using N2 physisorption (BET method), temperature-programmed calcination (TPC), temperature-programmed reduction (TPR), temperature-programmed oxidation (TPO), temperature-programmed desorption (TPD), X-ray diffraction (XRD) analysis, X-ray photoelectron spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. The influence of different operation conditions including reactant partial pressure and temperature on catalytic performance of ethanol dry reforming was also studied in this project. Promoted and unpromoted 10%Ni/Al2O3 catalysts were prepared by co-impregnation method and evaluated in a quartz fixed-bed reactor at different CO2:C2H5OH ratios of 2.5:1 to 1:2.5 and temperature of 923-973 K under atmospheric pressure. Promoted and unpromoted catalysts possessed relatively high BET surface area of about 71-108 m2 g-1 and both promoters were well dispersed on catalyst surface. Both NiO and NiAl2O4 phases were detected on the surface of promoted and unpromoted catalysts whilst CeO2 and La2O3 phases were observed for Ce- and La-promoted catalysts, respectively. The reduction of NiO species to metallic Ni0 phase occurred at two different reduction temperatures depending on the degree of metal-support interaction. Moreover, the acid site concentration was significantly reduced about 30.45% and 40.68% with the addition of Ce and La promoters, respectively. For catalytic evaluation, both C2H5OH and CO2 conversions enhanced considerably with growing reaction temperature from 923 to 973 K due to the endothermic nature of ethanol dry reforming reaction. The increase in CO2 partial pressure from 20 to 50 kPa improved reactant conversions for all catalysts whilst the optimal C2H5OH partial pressure was observed at 30-40 kPa depending on catalyst types. Interestingly, H2/CO ratio was always achieved within 1.1 to 1.9 regardless of operation conditions suitable for downstream Fischer-Tropsch synthesis. Irrespective of operating parameters, La-promoted catalyst appeared to be the best catalyst in terms of H2 yield and 3%La loading was the optimal promoter loading for La-doped catalysts because of the high mobile oxygen storage capacity of La2O3. 3%La-10%Ni/Al2O3 catalyst also seemed to be stable for 24 h on-stream at stoichiometric feed composition and reaction temperature of 973 K in terms of reactant conversion and H2/CO ratio. The heterogeneous nature of deposited carbons was evident with the presence of both amorphous and graphitic carbons on spent catalyst surface. However, the percentage of deposited carbon was reduced with promoter addition in the order; La-promoted< Ce-promoted < unpromoted 10%Ni/Al2O3 catalysts. At the end of this research, all the objectives that were set out have been achieved completely.